Children's rights : from philosophy to public policy - Cowden, Mhairi, 1986- (Houndmills, Basingstoke, Hampshire ; New York, NY : Palgrave M acmillan, 2016)
"Despite the existence of the UN Convention on the Rights of the Chi ld there is still a debate about whether children can really hold right s. This book presents a clear theory of children's rights by examining controversial case studies. Understanding why children have rights pres ents a pathway to translating rights into practical social and politica l instruments for change"--
Preface -- Introduction -- What is special about children? -- Why ch ildren do not hold rights -- Capacity and competence -- Why children ha ve rights -- A right to develop -- A right to know -- A right to medica l decision making -- A right to be loved -- A future for children's rig hts -- References -- Index.
Includes bibliographical references (p.175-217) and index.
Keywords: Children's rights; Children -- Government policy